2008
DOI: 10.1073/pnas.0807569105
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the chemotactic response of Escherichia coli to time-varying stimuli

Abstract: In their natural environment, cells need to extract useful information from complex temporal signals that vary over a wide range of intensities and time scales. Here, we study how such signals are processed by Escherichia coli during chemotaxis by developing a general theoretical model based on receptor adaptation and receptor-receptor cooperativity. Measured responses to various monotonic, oscillatory, and impulsive stimuli are all explained consistently by the underlying adaptation kinetics within this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
344
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(364 citation statements)
references
References 36 publications
13
344
0
1
Order By: Relevance
“…coli's chemotaxis signalling network, as described in the model of Tu et al [33], though different from these transcriptional networks, was found on theoretical grounds to exhibit the FCD property [72]. This was tested experimentally in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…coli's chemotaxis signalling network, as described in the model of Tu et al [33], though different from these transcriptional networks, was found on theoretical grounds to exhibit the FCD property [72]. This was tested experimentally in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Chemotaxis Signaling Pathway Model : The chemotaxis signaling pathway of E. coli was modeled with three major components, and their corresponding models were adapted from recent studies 37, 38, 39, 40, 41, 42, 43. The first component, MCP complex, was represented with a Monod–Wyman–Changeux (MWC) model52 to describe the allosteric effects of receptor clusters with identical receptors.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, the taxis‐based guiding method constitutes the major way to regulate the otherwise highly stochastic motion of bacteria‐driven microswimmers, which has been studied both in vitro17, 20, 21, 22, 23, 24, 25 and in vivo 14, 16. Chemotaxis, one of the most common taxis behaviors in bacteria, has been well understood36 and its signaling pathway has been mathematically modeled 37, 38, 39, 40, 41, 42, 43. In general, the chemotaxis of free‐swimming bacteria associates with a biased random walk, enabled by preferentially suppressed tumble tendency when the bacteria travel up a chemoattractant gradient; whereas in an uniform medium, the tumble tendency is isotropic over all swimming directions.…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour is interpreted as a change from a low background concentration response regime, where the bacteria respond to absolute changes in concentration to a high-concentration response regime, where they respond to relative change in concentration ('logarithmic sensing'), as previously observed [26]. Semi-empirical mean-field models have been developed [22,27,37] to explain the large dynamic range of the chemotaxis system. The chemoreceptors cluster in groups of dimers, containing N Tar receptor dimers, which form active or inactive complexes, responding according to an allosteric two-state model to attractant binding [38].…”
Section: Creating a Chemical Gradientmentioning
confidence: 99%